Assessment of the meiofaunal assemblages in a NaGISA rocky shore site in Taklong Island, Southern Guimaras, Philippines (2013). - Superio, Jushua L.
This study was conducted on a rocky shore site in Taklong Island National Marine Reserve (TINMAR), Southern Guimaras. (10"24' - 10"26' N and 122"29'-122"31' E). Field sampling was done in September 2013, with four transect lines laid according to depth gradients of high tide (THT) with five replicates, mid tide (TMT) with four replicates, low tide (TLT) with four replicates and 1m (TST) levels with four replicates samples taken at every five meters of each transect. Forty-three taxa were identified with harpaticoid copepods as the numerically dominant taxa were identified with harpaticoid copepods as numerically dominant taxa comprising 56.63% of the total meiofauna found in the sampling area, followed by nematodes (27.58%), syllids (6.59%), turbellarians (1.67%0 and ostracods (1.42%) respectively. The overall mean density of meiofaunal assemblage was 16,810.4 ind.*m-2 (sd=5288.29). High tide transect (THT) had the highest mean density of 31,692 ind.*m-2 (sd=12726.9) whereas sub-tidal transect (TST) had the lowest mean density of 8,569.6 ind.*m-2 (sd=1355.03). Also, harpacticoid copepods were the major contributot of meiofauna in almost all transect except in high tide transect (THT)which was dominated by nematodes. In addition, meiofaunaldensity increased as water depthdecreased. This trend can be expalined by the affinity of meiofaunal organisms tosediments, where intertidal was characterized by presence of more sediments campared to subtidal. Sediments tend to increase the density and diversity of meiofaunal communities by increasing habitat diversity and encouraging colonisation by species. Further, one way analysis of variance (ANOVA) showed a high variablity in each tidal level and a significant difference (F=9.933; p=0.001) between tidal levels in total meiofaunal abundance while there was an inverse relationship between mean macroalgal biomass and overall mean meofainal density (R=-0.88017)